Geography and the Early Cistercian Exempla Collections - Mula, Stefano (2011)
The article examines the Cistercian exempla collections to investigate their geographical diffusion and to explore the changing role of exempla in the Cistercian milieu. It states that early collections have joined the local to the universal by putting together recent miracles and visions. It notes that the collection has been valued for their spiritual teaching outside the Order, while a unified past and common lore has been created inside the Order.
Keywords: Cistercian monasteries; Exempla; Miracles; Religious Literature; Visions